Peningkatan Keterampilan Digital Mahasiswa Program Pascasarjana Universitas Baturaja dalam Mendukung Pembelajaran Era 4.0 - Yunita Sari; Dadang Kurnia; Indah Purnomowati; Rani Anwar (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The era of the Industrial Revolution 4.0 demands skilled digital skills, including in the academic environment. Baturaja University Postgraduate Program students face challenges in utilizing digital technology to support more effective and efficient learning. This Community Service activity aims to improve the digital skills of Postgraduate Program students in optimizing learning platforms, managing academic data, and utilizing other supporting technologies. The methods used include interactive training, group discussions, and hands-on simulations. The material includes an introduction to digital technology, strategies for using learning applications, and digital-based information management skills. This activity involved initial and post-training skill evaluations to measure the improvement of participants' competencies. Results show a significant improvement in students' understanding and skills, especially in utilizing learning applications such as Learning Management System (LMS), virtual conference platform, and online collaboration tools. Participants were also able to manage learning materials more effectively and creatively. In conclusion, the improvement of digital skills directly contributes to students' ability to support technology-based learning processes in the 4.0 era. This program demonstrates the importance of strengthening digital competencies to address future academic and professional needs.